Male breast cancer a rare entity: the experience from North-East India - Das, Gaurav; Yadav, Jitin; Purkayastha, Joydeep; Talukdar, Abhijit; Khanna, Sachin (International Surgery Journal, 2019)
Background: Breast cancer is one of the most common malignancy among women but it is not common in men. Male breast cancer (MBC) is a rare disease and accounts for ∼1% of all cancers in men. There is lack of data related to MBC. The objective was to study the clinic-pathological characteristics and outcome of MBC patients at this institute. Methods: It is a retrospective study. Author analyzed clinico-pathological factors, management and follow up details of all patients with MBC from 2012 to 2018 at the cancer centre. Results: Total 20 patients were included in the study. No risk factor identified in any patient. The median age at diagnosis was 57.5 years. Most common location was central quadrant. Most common stage at presentation was stage 3. Fifteen patients underwent upfront surgery while neoadjuvant chemotherapy was given to two patients. One patient had complete pathological response (cPR). The median follow up was 24 months (4-60 months). Three patients developed local recurrence (3 chest wall and 1 axilla). Two patients developed distant metastasis (lung, liver and bone). Actual overall survival rate at 5 years was 67.5% with median disease-free survival was 55%. Conclusions: Multicentric trials are necessary to understand the predictive and prognostic markers and to improve the outcome in male breast cancer.